PENGARUH MEDIA PEMBELAJARAN PHET SIMULATION TERHADAP HASIL BELAJAR SISWA PADA MATERI PERUBAHAN ENERGI DI KELAS V SDN 1 BEUREUNUEN - Salsabila, Fathiya; Safiah , Intan; Fitriani, Suci (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low learning outcomes of students in the science subject of energy changes in grade V of SDN 1 Beureunuen are influenced by the use of less than optimal learning media and limited laboratory facilities. PhET Simulation media is seen as an alternative learning because it is able to visualize abstract concepts and replace the limitations of practical activities. This study aims to determine the effect of using PhETSimulation media on student learning outcomes in energy changes. This study uses a quantitative approach with a quasi-experimental method and a Non-Equivalent Control Group design. The research sample consists of class VA as the experimental class and class VC as the control class with a total of 36 students. Data collection was carried out through multiple choice tests. Data analysis includes calculating N-Gain as well as normality tests, homogeneity tests, and hypothesis testing using Mann-Whitney U. The results showed that the average N-Gain of the experimental class was higher than the control class. The hypothesis test produced a significance value (2-tailed) of 0.000 <0.05, so H₀ was rejected and H₁ was accepted. Thus, the use of PhET simulation media significantly impacted student learning outcomes in the topic of energy transformation.